Do not bet on your favourite football team: the influence of fan identity-based biases and sport context knowledge on game prediction accuracy. Issue 3 (27th May 2019) - Na, Sangwon; Su, Yiran; Kunkel, Thilo
ABSTRACT: Research question : While the influence of sport context knowledge, such as home advantage and team ranking, on prediction accuracy has been discussed in the previous literature, the role of identity-based biases, such as fans' level of team involvement and the selection of their favourite team, in betting behaviour remain unclear. The main purpose of this study is to develop an understanding of how sport fans' biases and sport context knowledge influence the accuracy of sport game predictions. Research methods : A smartphone application enabled us to collect real soccer game predictions and results. A total of 529 football fans participated in 53, 943 predictions of 2353 professional football games within a mobile smartphone application. Chi-square tests and logistic regressions were used to analyse the data. Results and findings : Chi-square test results indicate that individuals overestimate their favourite team to win, as well as they split their predictions into dichotomous outcomes by overestimating wins and losses and underestimating draws. Logistic regression analyses indicate that identity-based biases negatively influence prediction accuracy, whereas individuals' sport context knowledge positively contributes to prediction accuracy. Implications : The study contributes to our understanding of the Psychological Continuum Model, individual biases, social identity theory and the psychological concept of splitting. Findings have implications for organizations who need to understand fans' sport gambling behaviour and sport fans who seek to optimize their game prediction accuracy to improve their bets and fantasy team selections.